Bioactive Compounds with Leishmanicidal Potential from Helianthus tuberosus and Vernonanthura squamulosa - Rachel Nápoles Rodríguez; María Laura Arreguez; Aldana M. Corlatti; Hernán G. Bach; César A. N. Catalán; Laura C. Laurella; Paola A. Barroso; Valeria P. Sülsen (Molecules, 2025)
Leishmaniasis is a neglected tropical disease caused by protozoan parasites of the genus Leishmania. An estimated 700,000 to 1 million new cases occur annually. Current therapies are limited by high toxicity, cost, prolonged treatment period, and rising resistance in endemic regions. The Asteraceae family has emerged as a promising source of bioactive compounds with proven leishmanicidal activity. In this study, the assessment of the antileishmanial activity of Helianthus tuberosus and Vernonanthura squamulosa extracts, the isolation of the sesquiterpene lactones heliangin and glaucolide A, respectively, and the evaluation of the activity of the compounds were conducted. Dichloromethane extracts of H. tuberosus and V. squamulosa were active on Leishmania amazonensis promastigotes, inhibiting the replication of the parasites in 97.2 ± 3.1% and 89.1 ± 1.1%, respectively, at 100 μg/mL. Heliangin was active against promastigotes of L. amazonensis (IC50 = 9.3 μM) and intracellular amastigotes (IC50 = 0.8 μM), while glaucolide A exhibited moderate activity against promastigotes (IC50 = 46.7 μM) and did not show activity against intracellular amastigotes. Based on these results, heliangin was further evaluated in an animal model of cutaneous leishmaniasis using BALB/c mice infected with L. amazonensis. Heliangin (8 mg/Kg), when administered in combination with Glucantime, significantly reduced lesion progression and parasite load compared to the vehicle-treated group (p < 0.001). These findings show that heliangin is a potential candidate for leishmaniasis treatment, especially in combination with therapeutic drugs.